2010
DOI: 10.1111/j.1757-1707.2010.01041.x
|View full text |Cite
|
Sign up to set email alerts
|

An integrated biogeochemical and economic analysis of bioenergy crops in the Midwestern United States

Abstract: This study integrates a biophysical model with a county-specific economic analysis of breakeven prices of bioenergy crop production to assess the biophysical and economic potential of biofuel production in the Midwestern United States. The bioenergy crops considered in this study include a genotype of Miscanthus, Miscanthus  giganteus, and the Cave-in-Rock breed of switchgrass (Panicum virgatum). The estimated average peak biomass yield for miscanthus in the Midwestern states ranges between 7 and 48 metric to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
149
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 141 publications
(161 citation statements)
references
References 41 publications
(62 reference statements)
5
149
4
Order By: Relevance
“…Jain et al(2010) describe two scenarios for the costs of production of miscanthus and switchgrass, a low cost and a high cost scenarios. The benchmark case considered the low cost of miscanthus and switchgrass production described there.…”
Section: Vii3 Sensitivity Analysismentioning
confidence: 99%
“…Jain et al(2010) describe two scenarios for the costs of production of miscanthus and switchgrass, a low cost and a high cost scenarios. The benchmark case considered the low cost of miscanthus and switchgrass production described there.…”
Section: Vii3 Sensitivity Analysismentioning
confidence: 99%
“…However, there is currently a significant lack of understanding about the possible path and dynamics of this transition. Economists have worked rigorously on understanding the development of such a system using tools from macro-economics [7][8][9][10]. Although, it provides an excellent framework to identify or evaluate policy alternatives, these analyses often make simplifying assumptions that ignore the practical aspects of feedstock production system.…”
Section: Introductionmentioning
confidence: 99%
“…We are using the operating cost reported by Jain et al (2010) because the opportunity cost are endogenous to our model as opposed to exogenous (Huang et al, 2009;Jain et al, 2010;Aravindhakshan et al, 2010). For states that were not included in Jain et al (2010), we use the production cost reported by Aravindhakshan et al (2010) which results in operating cost of $38.13 per ton. For our analysis, we assume an upper and lower bound of +/-20% on this costs which results in $30 and $46 for the low and high cost scenarios, respectively.…”
Section: Crop Residues and Energy Cropsmentioning
confidence: 99%
“…Switchgrass (Panicum virgatum) yield data was obtained from Jager et al (2010) who provide the maximum of lowland and upland yield which was also used in the billion-ton study update (Perlack and Stokes, 2011). The cost of producing switchgrass is taken from Jain et al (2010) who calculates the cost ranging from $39 to $90 per dryton for eight Midwestern states 2 . We are using the operating cost reported by Jain et al (2010) because the opportunity cost are endogenous to our model as opposed to exogenous (Huang et al, 2009;Jain et al, 2010;Aravindhakshan et al, 2010).…”
Section: Crop Residues and Energy Cropsmentioning
confidence: 99%
See 1 more Smart Citation